Sociological perspective on the well-being of the elderly Muslim women in Malaysia - Lyndon, Novel; Shahizan Ali, Mohd. Nor; Mat Jali, Mohd. Fuad; Abdullah, Azlina; Areff, Nor Aisah (Institute of Advanced Science Extension (IASE), 2019)
There are a growing number of studies on the aging society in Malaysia. However, many of those employ quantitative approaches, which yield important data but concentrate more on the experts’ standpoint for which researchers’ perspectives possibly outweigh the importance of the subjects’. Therefore, this study was an attempt to analyses the meaning of well-being from the viewpoint of elderly Muslim women. The findings revealed that the elders perceived well-being as having the opportunities to learn and to teach. Apart from that, the ability to perform good deeds and to avoid any wrongdoings as ordered by Allah meant that they had gone through wellbeing. They also believed that they had achieved well-being for which to some elders experiencing happiness and peacefulness as the means to identify it. Finally, in viewing the meaning of well-being to elders, religion could be the most significant dimension. As the subject of religion could be identified throughout the thesis, it shows how religion becomes the part and parcel of elders’ personal and collective lived experiences. Subsequently, activity theory rooted in symbolic interactionism and gerotranscendence seemed to be more applicable in explaining elders’ interpretations of wellbeing. In conclusion, the construction of their worldview on well-being would give a better understanding of elders’ future needs in the local sociocultural environment. Thus, the efforts in policy planning and implementation could be expected to be more attentive to and effective for the Malaysian elders’ benefits